Effects of Teaching English Using Storytelling with Picture Series on Speaking Ability of 6th Graders - Chuenchomkun, Narudee; Waewchimplee, Waewalee (Journal for Developing the Social and Community, 2024)
Speaking English is very important for communicating with others around the world. Speaking allows people to share with others and express their thoughts and feelings to exchange information and students need to improve their speaking abilities for future needs in their careers or daily lives. This study is for teaching English using storytelling with picture series. It’s research objectives are 1) to study the efficiency of teaching English using picture-based storytelling on the speaking ability of grade 6 students, and 2) to study the satisfaction of teaching English by using pictures. Storytelling using pictures on the speaking ability of grade 6 students. The samples consisted of 36 sixth-grade students at Anuban Nakhon Ratchasima Primary School, under the Center of Educational Networks of Nakhon Ratchasima Primary Educational Service Area Office 1, Nakhon Ratchasima Province. The selected sample was cluster random sampling for the experimental group. The instrument used in the research procedure was the lesson plan, and the instrument used for data collection were 1) the English-speaking ability test and 2) the questionnaire as the tools for students’ satisfaction. The results of this study showed that after learning English using storytelling with picture series, the students’ English speaking ability post-test mean score was significantly higher than the pre-test. The students had positive satisfaction with learning English using storytelling with picture series.